Robust hand tracking for surgical telestration - Müller, Lucas-Raphael; Petersen, Jens; Yamlahi, Amine; Wise, Philipp; Adler, Tim; Seitel, Alexander; Kowalewski, Karl-Friedrich; Müller, Beat P.; Kenngott, Hannes Götz; Nickel, Felix; Maier-Hein, Lena (International journal of computer assisted radiology and surgery, 2022)
As human failure has been shown to be one primary cause for post-operative death, surgical training is of the utmost socioeconomic importance. In this context, the concept of surgical telestration has been introduced to enable experienced surgeons to efficiently and effectively mentor trainees in an intuitive way. While previous approaches to telestration have concentrated on overlaying drawings on surgical videos, we explore the augmented reality (AR) visualization of surgical hands to imitate the direct interaction with the situs.